Review of the genus Microtachycines Gorochov with two new species (Orthoptera, Rhaphidophoridae, Aemodogryllinae) from China - Qin, Yanyan; Liu, Xianwei; Li, Kai (Zootaxa, 2017)
This work involves a review of the genus Microtachycines, including descriptions of two new species: Microtachycines elongatus sp. nov., Microtachycines fallax sp. nov.. A key to the species of Microtachycines is presented.